Islamic ideology in the globalized world:a Nigerian Muslim experience - Ayuba, Mahmud Adesina (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2013)
The world has become a global village and resulted into unavoidable intermingling of habitat of different societies with diverse culture and religious backgrounds. This has been identified to be the major cause of global unrest. The main thrust of this study, therefore, is to look into the effects of globalization on Nigerian Muslims. Methodologies used in this study are sociological and moral approaches. The study found out that the sources of Islamic teachings are divine in nature, while that of globalization are not. The study also revealed that the distinctive approach of Islamic ideology is that its instructions are aimed at the general welfare of the whole world, while the proponents of globalization want to re-create a world idea on everything tailored towards their ideology and conception of what a unified world should be. The study blamed the existing moral decadence and social misconduct among the Nigerian Muslims on unguarded consumption of programs through global information and communication technologies. Some elements of globalization such as telecommunications system, entertainment through the mass media, internet, satellite, and computer, among others, are examined and revealed that they portend great danger to the continuous serenity of Nigerian Muslims. The study, therefore, recommended moderation and education on the part of the Muslims to be able to distinguish between the good and bad ideologies from the preaching of globalization and also calls on the government to censor and regulate national systems of communication in order to curb the negative effects of globalization on Nigerian citizens.